2004
DOI: 10.1097/00000478-200401000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Oral Plasmablastic Lymphomas in AIDS Patients Are Associated With Human Herpesvirus 8

Abstract: Human herpes virus type 8 (HHV8) has been strongly associated with Kaposi sarcoma, primary effusion lymphoma (PEL), and Castleman's disease. To our knowledge, infection by this virus has not been strongly associated with other hematopathologic malignancies. We examined five oral cavity lymphomas from men with AIDS for HHV8 and HIV-1 by reverse transcriptase in situ polymerase chain reaction, as well as for Epstein-Barr virus (EBV) (EBER-1, -2) using in situ hybridization and HHV8 protein with immunohistochemis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
73
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(74 citation statements)
references
References 20 publications
0
73
1
Order By: Relevance
“…They concluded that the HHV-8 DNA detected by PCR was most likely due to the presence of infected bystander circulating (non neoplastic) lymphocytes. 140 The discrepant findings, relative to those of Coic et al 137 in which HHV-8 was demonstrated in most of the tumour cells, may be attributed to differences in methodology and the HHV-8 antibody used. Carbone et al 141 were subsequently prompted to re-evaluate the possible presence of HHV-8 infection in plasmablastic lymphomas of the oral cavity.…”
Section: It Is Now Established That Other Forms Of Immunodeficiency/imentioning
confidence: 93%
“…They concluded that the HHV-8 DNA detected by PCR was most likely due to the presence of infected bystander circulating (non neoplastic) lymphocytes. 140 The discrepant findings, relative to those of Coic et al 137 in which HHV-8 was demonstrated in most of the tumour cells, may be attributed to differences in methodology and the HHV-8 antibody used. Carbone et al 141 were subsequently prompted to re-evaluate the possible presence of HHV-8 infection in plasmablastic lymphomas of the oral cavity.…”
Section: It Is Now Established That Other Forms Of Immunodeficiency/imentioning
confidence: 93%
“…Cases of plasmablastic microlymphoma, an emerging phenomenon described in HIV-infected patients often with preexistent multicentric Castleman disease, were excluded from this study. HHV8-positive PBL cases were also excluded from the analysis as great controversy in the present literature exists as to the role of this oncovirus in PBL pathogenesis [38,39,[48][49][50][51]. Unpublished data and cases reported in abstract form only were also excluded.…”
Section: Methodsmentioning
confidence: 99%
“…These tumors are generally associated with EBV and HHV-8 (10). Response to conventional chemotherapy is poor and some investigators have suggested that viral targeted approaches may be beneficial [12].…”
Section: Subtypes Of Aids Nhlsmentioning
confidence: 99%